2010
DOI: 10.1002/ca.21043
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the course and microanatomical study of the lateral femoral cutaneous nerve and its clinical importance

Abstract: The lateral femoral cutaneous nerve (LFCN), a branch from the lumbar plexus, may come to the clinician's or surgeon's attention. We studied this nerve to determine its location and its relationship with neighboring structures around the anterior superior iliac spine (ASIS) and the inguinal ligament (IL). Additionally, cross-sectional microanatomy of the LFCN at the IL was studied. The LFCN was dissected in 47 lower limbs from formalin-fixed cadavers. The distances from the ASIS to the point where the LFCN cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 38 publications
2
35
2
2
Order By: Relevance
“…Others noted that the anatomy of the membranous layer varied with sex, adiposity, and body region 45 and that it was thicker in the lower compared with the upper extremity and on the posterior compared with the anterior aspect of the body 46 . Many anatomical studies have described the LFCN anatomy and its variations in relation to the ASIS, the approach for iliac crest bone harvesting, or the surgical management of meralgia paresthetica [19][20][21][22][23][24][25][26]40 . In the present study, most LFCN branches entered the thigh above (27%) or medial to (62%) the ASIS.…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
See 1 more Smart Citation
“…Others noted that the anatomy of the membranous layer varied with sex, adiposity, and body region 45 and that it was thicker in the lower compared with the upper extremity and on the posterior compared with the anterior aspect of the body 46 . Many anatomical studies have described the LFCN anatomy and its variations in relation to the ASIS, the approach for iliac crest bone harvesting, or the surgical management of meralgia paresthetica [19][20][21][22][23][24][25][26]40 . In the present study, most LFCN branches entered the thigh above (27%) or medial to (62%) the ASIS.…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
“…The nerve pierces the fascia lata beneath the inguinal ligament and runs laterally and distally within the subcutaneous tissue of the anterolateral region of the thigh 18,19 . The exit from the intrapelvic passage or entry into the thigh region can vary, as several anatomical studies have shown [19][20][21][22][23][24][25][26] . While most anatomical textbooks do not describe the distribution pattern of the LFCN in the proximal aspect of the anterolateral thigh region [27][28][29][30] , some authors describe a division of the LFCN into an anterior (femoral) and posterior (gluteal) branch after passing behind or through the inguinal ligament 18,23,24,31 .…”
mentioning
confidence: 99%
“…sartorius muscle laterally in 64.5% (12). Origin of the LFCN from the femoral nerve has been noticed in 6% (1) to 10% (13) of the studied cases, whereas there is a documented case in which the LFCN was found arising from the femoral nerve, although the origin occurred below the level of the IL (3).…”
Section: Natsis K Et Al: Variable Origin and Ramification Pattern Ofmentioning
confidence: 87%
“…It is important for the orthopaedic surgeon to be aware of these branches, their course and variations in their branching, as injury to the LFCN branches may cause thigh numbness post surgery. 4,19,20 The LFCN exits the pelvis and then sends branches medially across the sartorius muscle, 2 to 3 cm distal to the ASIS. 21 For the purpose of this study, it is necessary to identify the inguinal ligament, as the LFCN passes deep to the inguinal ligament before it can be identified over the sartorius muscle (Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
“…The complications that may arise if the high learning curve is not overcome is the possibility of thigh numbness if the LFCN or any of its branches are cut. 19,20 Death could also result if the LCFA is severed. 6,8 In the attempt to demonstrate the possible ease of performing hip arthroplasty using the anterior approach, it was necessary to request the assistance of a surgeon with experience in both the anterior and the anterolateral approach.…”
Section: Orthopaedic Simulationmentioning
confidence: 99%